2013
DOI: 10.1063/1.4793535
|View full text |Cite
|
Sign up to set email alerts
|

Negative gate-bias temperature stability of N-doped InGaZnO active-layer thin-film transistors

Abstract: Stability of negative bias temperature stress (NBTS) of nitrogen doped amorphous InGaZnO (a-IGZO) thin-film transistor (TFT) is investigated. Undoped a-IGZO TFT stressed at 333 K exhibit a larger negative ΔVTH (−3.21 V) with an unpredictable sub-threshold swing (SS) of hump shaped transfer curve due to the creation of meta-stable traps. Defects related hump formation has disappeared with small ΔVTH (−1.13 V) and ΔSS (0.018 V/dec) in nitrogen doped a-IGZO TFT. It is observed that nitrogen doping enhances device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 22 publications
7
66
0
Order By: Relevance
“…In our previous study [25], we designed a-IZO/a-IGZO:N TFTs, whose µFE was quite large (49.6 cm 2 ·V −1 ·s −1 ), but VTH was too negative (−2.3 V). In this study, however, Sample II (a-IZO:N/a-IGZO:N TFT) had a positive VTH of 1.5 V, which might result from the fact that N-doping decreased the trap states in a-IZO and at the front channel interface [12,13]. As shown in Figure 5a,b, the N-doped DSCL TFTs (Samples I and II) showed different PBS stability.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…In our previous study [25], we designed a-IZO/a-IGZO:N TFTs, whose µFE was quite large (49.6 cm 2 ·V −1 ·s −1 ), but VTH was too negative (−2.3 V). In this study, however, Sample II (a-IZO:N/a-IGZO:N TFT) had a positive VTH of 1.5 V, which might result from the fact that N-doping decreased the trap states in a-IZO and at the front channel interface [12,13]. As shown in Figure 5a,b, the N-doped DSCL TFTs (Samples I and II) showed different PBS stability.…”
Section: Resultsmentioning
confidence: 79%
“…Conventional AOS TFTs, i.e., the devices with single channel-layers (a-IGZO TFTs, a-IGZO:N TFTs, etc. ), generally have µ FE of less than 10 cm 2 ·V −1 ·s −1 [10,12,31]. The N-doped DSCL TFTs (Samples I and II), however, exhibited apparent improvements in their field-effect mobilities, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently it was reported that the nitrogen-doping process could effectively improve the subthreshold swing (SS) and device stability of a-IGZO TFTs while simultaneously causing the mobility loss due to the suppression of oxygen vacancy (Vo) and trap density in the bulk channel layers [5]. On the other side, the double-stacked channel layers (DSCL) were also proved to be effective in making a-IGZO TFTs more stable by our group and the other researchers [6,7].…”
Section: Introductionmentioning
confidence: 99%